3D printing conformal metasurface for Fabry‐Perot resonator antenna application. Issue 6 (28th March 2021) - Xie, Peng; Wang, Guangming
Abstract: A conformal receiver‐transmitter metasurface (MS) for high gain conformal Fabry‐Perot (FP) resonator antenna is presented in this article. The meta‐atom consists of three layers of metal structures and two layers of supporting structures. The three layers of metal structures, including receiver patch, radiator patch and ground plane, are printed on ultra‐thin substrates. The reception and radiation of the meta‐atom are separated by the ground plane, in which case, the reflection and transmission coefficients of the meta‐atom can be tuned independently. This property enables the MS to realize transmission phase compensation while maintain the reflection coefficient constant. Also, the supporting structures are fabricated by 3D printing technology, thus they can be fabricated into cylinder and the metal structures on ultra‐thin substrates are easily conformed to them. A conformal patch feed antenna is designed in the same way. Then the conformal FP resonator antenna is formed by the MS and the feed antenna. Through tuning the transmission phase of each meta‐atom, the MS can make the wave coming out of the cavity appear as a nearly plane wave. The peak gain of the conformal FP resonator antenna reaches 18 dB with aperture efficiency of 58.5%. Fine radiation pattern and high gain property are obtained by the conformal resonator antenna. The measured results verify the performance of the proposed conformal antenna. The design in this article can greatly promote the practical application of the FP resonator antenna.